Factors Affecting Knowledge of Emergency Contraception among Addis Ababa University Female Students, Addis Ababa, Ethiopia - Mariye, Yitbarek Fantahun; Fasil, Nebiyou; Bisrat, Mekedem Hailemariam; Weldetensaye, Eskinder Kebede (Ethiopian Journal of Reproductive Health, 2023)
Background: The prevalence of unintended pregnancy is very high in Ethiopia and young and adolescents are one of the major groups that are affected by it. The lack of knowledge of emergency contraception methods is one of the contributing factors to the increasing prevalence of unintended pregnancy. In this study, we explored the level of awareness and the factors affecting the knowledge of one of the most vulnerable groups in our society, university students. Objectives: To assess the level of knowledge as well as factors affecting Knowledge of emergency contraception among female students. Methods: An institution-based cross-sectional study was conducted at Addis Ababa University. The sample size calculated was 648. Data was collected by a self-administered questionnaire and data was entered, cleaned, and analyzed using SPSS version 21. Descriptive statistics was performed to get frequency and percentages. Logistic regression and Chi-square analysis were used to identify predictors of the outcome variable. Result: A total of 648 students were included in the study giving a response rate of 100%. Of all the respondents, 111 (17%) were sexually active, 439 (68%) have ever heard about and 158 (24.5%) have ever used emergency contraception methods. Of those respondents who ever heard of emergency contraceptive methods 265 (60%) (95% CI: 58%, 62%) were found to have good knowledge. The study has shown that field of study (AOR, 7.24; 95% CI: 4.103,12.772, P < 0.000) and every use of emergency contraceptive methods (AOR, 2.075; 95% CI: 1.234,3.490, P < 0.006) were significantly associated with having good knowledge of emergency contraceptive methods. Conclusion and recommendation: The level of knowledge about emergency contraception is fair. This study showed, that faculty of study and every use of emergency contraception are found to have a significant association with good knowledge of emergency contraceptive methods. Even though the knowledge of the respondents is fair much has to be done to improve their knowledge of the different methods by preparing a reproductive health education lesson, especially for students in non-medical faculty who may have been unaddressed.